Evaluation of Anti-Inflammatory Activities of Ethanolic Extract of Curcuma longa Rhizome in Rodent Models - Syarifudin, Aminah; Arsita, Cici (PCJN: Pharmaceutical and Clinical Journal of Nusantara, 2025)
Inflammation is a biological response to tissue injury or infection that often requires long-term management. Although synthetic anti-inflammatory drugs are effective, their prolonged use may cause adverse effects, highlighting the need for safer natural alternatives. Curcuma longa L. has been traditionally used for the treatment of inflammatory conditions. This study aimed to evaluate the anti-inflammatory activity of the ethanolic extract of Curcuma longa rhizome using a carrageenan-induced paw edema model in rats. An in vivo experimental study was conducted using male white rats (Rattus norvegicus). The animals were divided into five groups: negative control (0.5% CMC), positive control (diclofenac sodium 10 mg/kg BW), and three treatment groups receiving the ethanolic extract at doses of 100, 200, and 400 mg/kg BW. Paw edema was induced by carrageenan injection, and paw diameter was measured at 0, 2, 4, and 6 hours. Anti-inflammatory activity was expressed as the percentage of inflammation. The ethanolic extract of Curcuma longa significantly reduced inflammation compared to the negative control at all observation times. The 200 mg/kg BW dose exhibited the most effective and consistent anti-inflammatory activity, while a higher dose did not provide additional benefit. The ethanolic extract of Curcuma longa rhizome possesses significant anti-inflammatory activity, with an optimal effect observed at 200 mg/kg BW, supporting its potential as a natural anti-inflammatory agent.